]“Angolan Guerrillas and Eastern-European Live Experiences: a Prosopographical Approach (1961-1974)”, in: Chris Saunders, Helder Adegar Fonseca and Lena Dallywater (eds), Southern African Liberation Movements and the Global Cold War “East”. Transnational Activism 1960-1990, - Fonseca, Helder Adegar (2019)
This chapter is concerned with the experiences of Angolan `freedom fighters’ who underwent military training in socialist countries, and the impact of those experiences on the Liberation Struggle. Drawing on Portuguese Military and Policy Security Services interrogation Reports covering the period 1961-1974, this prosopographical history of a small group of Angolan fighters and people from other Liberation Movements explores three aspects: the geography and types of military training outside Southern Africa; what happened to Angolan military trainees in what were often regarded as “progressive” and “socialist” Meccas; and, by comparison, the experience in the so-called “heaven” of the “Simferopol” military camp in Crimea. Three main arguments will be developed: the impact of Eastern and Russian socialist assistance on a specific group of Liberation Movements, including the MPLA; the positive vision of life experienced by the military trainees in socialist society; and military training in the socialist world as an opportunity for social promotion in the guerrilla army, and as legacy.